Do Microorganisms in Bathing Water in Guadeloupe (French West Indies) Have Resistance Genes? - Degrâce Batantou Mabandza; Edlyne Colletin; Christophe Dagot; Isaure Quétel; Sébastien Breurec; Stéphanie Guyomard-Rabenirina (MDPI AG, 2024)
Waterborne faecal contamination is a major public health concern. The main objectives of this study were to investigate faecal contamination and Escherichia coli (E. coli) antibiotic resistance in recreational fresh water from Guadeloupe and to characterise the microbiome and resistome composition in biofilms from submerged rocks. Significant faecal contamination was observed at 14 freshwater sites. E. coli predominated (62%), followed by Enterobacter cloacae (11%) and Acinetobacter spp. (11%). Of 152 E. coli isolated, none produced extended-spectrum beta-lactamases (ESBLs), but 7% showed resistance to streptomycin and 4% to tetracycline. Biofilm resistome analysis revealed clinically significant antibiotic-resistance genes (ARGs), including those coding for resistance to sulfonamides (sul1), carbapenems (blaKPC), and third-generation cephalosporins (blaCTX-M). Mobile genetic elements (MGEs) (intI1, intI2, intI3) linked to resistance to aminoglycosides, beta-lactams, tetracycline, as well as heavy metal resistance determinants (copA, cusF, czcA, merA) conferring resistance to copper, silver, cadmium, and mercury were also detected. Diverse bacterial phyla were found in biofilm samples, of which Proteobacteria, Bacteroidetes, Planctonomycetes, and Cyanobacteria were predominant. Despite the frequent presence of E. coli exceeding regulatory standards, the low levels of antibiotic-resistant bacteria in freshwater and of ARGs and MGEs in associated biofilms suggest limited antibiotic resistance in Guadeloupean recreational waters.